INSTITUTIONAL MECHANISMS OF POLITICAL INTERACTION BETWEEN THE EUROPEAN UNION AND LATIN AMERICA IN THE CONTEXT OF THE TRANSFORMATION OF THE GLOBAL ORDER - Kolomoiets, Ihor (Public Management and Policy, 2026)
Ongoing changes in the global order and the growing competition among major international actors have significantly affected the ways in which supranational entities shape and implement their external policies. In this environment, the European Union has increasingly relied on institutional and political instruments to strengthen its engagement with strategically important regions, including Latin America. Global Gateway initiative reflects this shift by bringing together political priorities, investment instruments, and infrastructure cooperation within a single framework of external partnership. The purpose of this article is to examine the institutional mechanisms that underpin political interaction between the European Union and Latin America, with particular attention to the role of Global Gateway in contemporary international relations. The study focuses on how EU external policy towards the region is formulated and coordinated through the interaction of key supranational institutions. The analysis highlights the role of the European Council and the Council of the European Union in defining strategic orientations, the coordinating function of the European External Action Service, and the practical involvement of the European Commission in implementing partnership initiatives, notably through the NDICI – Global Europe instrument. Attention is also given to the role of the European Parliament in providing political oversight and democratic legitimacy to the EU’s external engagement. The article argues that Global Gateway should be viewed not merely as an investment or connectivity initiative, but as part of a broader transformation of the European Union’s external policy model. Its implementation contributes to deeper political interaction with Latin American countries by combining the EU’s normative foundations with pragmatic instruments of international influence and by creating institutional conditions for long-term strategic partnership.